2017
DOI: 10.1152/advan.00119.2017
|View full text |Cite
|
Sign up to set email alerts
|

Lecture attendance improves success in medical physiology

Abstract: The educators have underlined the importance of lecture attendance for decades. Nowadays, students have ample online educational sources, which began a debate on the necessity of in-class lectures. In the present study, we investigated the influence of lecture attendance on the exam success. To this aim, we adopted a novel approach and matched second-year medicine students' answers in three interim exams with the lectures related to those questions. Thereby, we were able to evaluate if attending lectures incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…Three studies showed moderate associations ( (Hamdi, 2006;Jaykaran et al, 2011;Stegers-Jager et al, 2012), one study showed moderate to weak associations (Al Khaja et al, 2019) and one study showed a weak association between lecture attendance and academic outcomes (Demir et al, 2012). In addition, one of the studies using correlation analysis was able to show that the students had better outcomes for the lectures they attended than for the ones they skipped, and that this was true for both the first-time and repeat takers (Demir et al, 2017).…”
Section: Positive Relationship Between Lecture Attendance and Academimentioning
confidence: 99%
“…Three studies showed moderate associations ( (Hamdi, 2006;Jaykaran et al, 2011;Stegers-Jager et al, 2012), one study showed moderate to weak associations (Al Khaja et al, 2019) and one study showed a weak association between lecture attendance and academic outcomes (Demir et al, 2012). In addition, one of the studies using correlation analysis was able to show that the students had better outcomes for the lectures they attended than for the ones they skipped, and that this was true for both the first-time and repeat takers (Demir et al, 2017).…”
Section: Positive Relationship Between Lecture Attendance and Academimentioning
confidence: 99%
“…In the 2010 meta-analysis, the positive relationship between lecture attendance and academic performance was also observed for the subgroup of 11 studies of students studying science [2]. The individual studies for students of the biological sciences included in the metaanalysis and subsequent studies of these students have mostly shown a positive association between lecture attendance and academic outcomes [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], but some have not [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Mandating students' attendance in classrooms has been, and continues to be a disputable issue, particularly for dental schools. Available literature on students' attendance patterns is scarce and there is no agreement between scientists about the potential impact, if any, on the academic performance of students (Alghamdi et al, 2016;Credé et al, 2010;Demir et al, 2017). А significant number of studies supported inclass attendance and demonstrated its importance for academic success.…”
Section: Discussionmentioning
confidence: 99%